Appropriation of Symbol as Disclosure of the World of the Play in Tennessee Williams’s “The Glass Menagerie” - Astrauskienė, Jurgita; Šležaitė, Indrė (Respectus Philologicus, 2013)
This paper examines the symbol as a key to understanding the world of Tennessee Williams’s play The Glass Menagerie (1945) within the frame of hermeneutics offered by Paul Ricoeur. Various conceptions of the symbol are presented, and the impact of religion upon the playwright’s drama is discussed. The interest of the authors is particularly directed towards the role of Christian symbols and their power to present, in a distinctive and irreplaceable way, the interplay of sacred and profane contexts. The Christian images inspire and shape the narrative structure of the drama. The analysis of particular symbols reveals that the playwright artistically uses Christian iconographic and liturgical implications as the symbolic pattern of the play. The spiritual meanings are evoked by the symbol of the rose, which is traditionally regarded as an emblem of the Virgin Mary, while the symbolic representation of the unicorn is associated with the Annunciation.
Keywords: Symbol; Hermeneutics; Appropriation; World of the Text; Religion; Myth